Evaluasi Resiko Kerja Pada Operasi Well Service Pada Sumur X Di Lapangan Kalrez Petroleum (Seram) Ltd - Ona Latumainase; Purnomosidi Purnomosidi; Erwin B. Pattikayhatu (Journal Mechanical Engineering, 2023)
During the process of producing fluid from a well, there is often a decrease in productivity which is caused by several things so that production often does not meet the specified targets. Therefore, Work Over Well Service (WOWS) is carried out to launch and maintain oil production in wells. In this WOWS activity, of course there are many potential hazards. Therefore, it is important to pay attention to work safety and all aspects of K3 starting from from work safety at height, work safety in flammable or explosive areas, electrical work safety, to well rework. In the data processing process, calculations are made of the processing time at the workover and well services activity program stages as well as the potential hazards that occur. This calculation refers to the standard processing time that has been set by the company's workover and well service. The aim is to obtain data. By utilizing field observation data, it is hoped to obtain actual information regarding workover and well service operating conditions and find possible anomalies. This is important to identify problems and find alternative solutions to well problems. From the results of research on work risk evaluation in well service operations carried out at Kalrez Petroleum (Seram) LTD, to find out priority risks, you must carry out calculations on the risk matrix by multiplying the probability and consequence values. The results of this calculation are potential dangers in service work activities. above the well. However, it is included in the low probability category, because work accidents occur within 5 (years) per 1 accident. So the risk control carried out can be said to be able to control risks in Work Over Well service activities, and monitoring and evaluation have been carried out well so far.  Keywords: Work Over & Well Service, Evaluation, Work risks.